Nilai-Nilai Pendidikan Akhlak Dalam Buku ‘Aisyah Karya Sulaiman An-Nadawi - Meilatisari, Risma; Agung, Ahmad; Hayatunnufus, Alifa Baiduri (Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID), Ciamis, Jawa Barat, Indonesia, 2020)
'Aisyah is a noble figure who should be exemplary. Many things can be taken from Aisyah RA, especially in terms of her personality. This can be used as a guide in dealing with the current problem of moral degradation. Through the book 'Aisyah by Sulaiman an-Nadawi, we can find out the values ​​of moral education contained in his life. This study seeks to elaborate on the values ​​of moral education in the book 'Aisyah by Sulaiman an-Nadawi, and how the relevance of the values ​​of moral education to modern life today. This research type is qualitative (literature review) with analytical descriptive method. Descriptive research is research that attempts to describe an event and aims to present a description of various problems. In this research, the writer tries to describe or describe the contents of the book entitled 'Aisyah by Sulaiman an-Nadawi in depth, especially regarding the values ​​of moral education contained in it. Based on the research that has been done, the value of moral education contained in the book 'Aisyah can be collected, namely; there is moral education such as qanaah, helping women, being obedient to husbands, keeping yourself from cheating, being wara` and refusing to accept gifts, being brave and having a high ethos, kind and generous, keeping yourself from trivial things, and always pay attention to the hijab. This is very important for us to follow in modern life today. The values ​​of moral education in the book 'Aisyah by Sulaiman an-Nadawi are very relevant in today's modern life, so the morals of Sayyidah' Aisyah Radiyallahu 'Anha must be an example for us in today's modern life.